Effect of the Empowerment Program on Muscle Exercise Practicing for Physical Disability Person Among the Village Health Volunteers - Srijai , Panida; Narin , Rangsiya; Aungwattana , Sivaporn (Nursing Journal CMU, 2020)
Physical disability person had health problems from complications such as muscle atrophy and join stiffness. It is very important and necessary to prevent these complications. Village health volunteers is a helper and health personal whom is near physical disability person and family in community. Therefore, village health volunteers should be developed ability in properly muscle exercise practicing for physical disability person. This quasi-experimental research aimed to study the effect of the empowerment program on muscle exercise practicing for physical disability person implemented by village health volunteers. Twenty-three participants were selected through purposive sampling technique from village health volunteers who were trained in a 70-hour course on providing care for older people organized by the Ministry of Public Health, works and provides services for physical disability person in Saraphi district, Chiang Mai province. The research instruments were consisted of 1) Empowerment program 2) Guide book on muscle exercise practicing and 3) Evaluation form on muscle exercise practicing which developed by researcher and tested for content validity indexes 0.83. The reliability of the instrument is based on the feasibility test of Richardson 21(KR-21) were 0.93. The statistical analysis of the frequency distribution, percentage, mean and the Wilcoxon signed-rank were used for data analysis. The research findings revealed that: The mean score of muscle exercise practicing for physical disability person was significantly higher after program participation (p < 0.001). There was a rise in the mean score on muscle exercise practicing before the program (=23.26, S.D.=3.22) and after the program (=44.47, S.D.=4.66). The results showed that research findings can be used as a guideline to promote community nurses and health care teams to reinforce the empowerment among village health volunteers to promote muscle exercise practice with effectiveness and efficiency for physical disability person. Suggestions for further research should be study on the outcomes for physical disability person such as degree of joint in motion, muscle strength, in order to promote the provision of quality health care services for physical disabilty person in community.